Microrganismos promotores de crescimento e adubação nitrogenada em Megathyrsus maximum cv. Brs Quênia - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
Brazil has extensive grassland areas for livestock, where sustainable practices have been adopted to increase productivity and reduce environmental impacts. Among these alternatives, the use of growth-promoting microorganisms in forage crops stands out. This work aimed to evaluate the efficiency of inoculation with Azospirillum brasilense and Pseudomonas fluorescens, associated with different doses of nitrogen, in the development of Kenya grass (Panicum maximum cv. Kenya). The experiment was conducted at Universidade Estadual de Goiás, Câmpus São Luís de Montes Belos, in a randomized block design, factorial scheme 2 4, with eight treatments and four repetitions. Morphological and physiological variables were evaluated, including plant height, number of tillers, leaf/stem ratio, productivity and chlorophyll content. The results showed no statistically significant differences (P > 0.05) between treatments; however, consistent trends of benefits of inoculation and nitrogen fertilization were observed. The significant correlations between physiological and productive variables reinforce the importance of an integrated approach in the evaluation of forage performance. It is concluded that, although the effects have not been statistically proven, the combined use of bioinoculants and nitrogen fertilization has potential to contribute to the sustainability and efficiency of pasture production.
Microorganisms promoting growth and nitrogen fertilization in Megathyrsus maximum cv. Brs Quenia
Keywords: Adubação nitrogenada; Panicum maximum; Azospirillum brasilense; Pseudomonas fluorescens; Forragicultura; Nitrogen fertilization; Kenya grass; Azospirillum brasilense; Pseudomonas fluorescens; Forage farming; CIENCIAS AGRARIAS